Is the human physiological boundary coming? An analysis of world records` progression and future - Feng, D.; Cao, T. Y. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
Purpose: The author used mathematical models to analyze world records in track and swim events in order to found out the social factors, economic factors, historical factors and scientific factors that have affected the progression of world records. Method:1825 pieces of swimming and track events world records were analyzed by ARIMA model and independent sample t test. ARIMA model demonstrated the following characteristics: new WR rate rose in 1912-1928 years initially, then the rate began to decline; the second rise period started in 1943, the rate began a downward trend after 1976 except that in 2008 and 2009, the new WR rate was much higher than average number compared to the year between 1976-2014. The results also showed 4 periods of troughs in new WR rate: the first period was 1913-1918, the second was 1939-1946, the third was 1990-1997, and the last one was 2010-2014. In following 30 years, the probability of new world records will be maintained at a stable and very low level of rate (0.16), provided the human gene and morphology, technology and other conditions are not changed. The other finding of this paper was that annual mean of new WR of events started after 1950 was almost 2 times than that of events started before 1950. Conclusions: Science and technology were the driving factors for the improvement of new WR rate; war seriously hindered the development of sports; doping was contributed to the peak period of new WR rate; the combination of sports and business changed sports training and competition theories, consequently, athlete`s body becomes more fragile, and sports life shortened. The reasons for swim events showing higher annual mean of new WR than track events are the differences in sports techniques, movement environment and the sports mechanics.